Pola Pendidikan Karakter Pada Masa Pandemi di Pondok Pesantren Makrifatul Ilmi Bengkulu - Sofa, Mochamad Lutfan; Azis, Ahmad Bahrudin; Asiyah, Asiyah (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
Islamic boarding schools are educational institutions in the midst of society that are at the forefront of launching character education for students, especially during the current Covid-19 pandemic. This research on character education was conducted at the Makrifatul Ilmi Islamic boarding school, South Bengkulu with the aim of knowing the values instilled in students in the formation of their character as well as the supporting and inhibiting factors. The method used in this research is descriptive content analysis with the type of field research. Thus, the results of the study indicate that the implementation of character education during the pandemic at the Makrifatul Ilmi Islamic Boarding School South Bengkulu is carried out in the classroom and outside the classroom, which includes the cultivation of religious values, independence, humility, honesty, respect for achievement, love for the environment, social care, creative, likes to read, tolerance, responsibility, discipline, cooperation, hard work, and creativity. To realize these character values, the example of educators is very decisive. Therefore, educators are expected to be able to improve their functions in terms of educating, guiding, directing, training, and motivating so that students are accustomed to behaving with good character values.